A new metabolic comorbidity score predicts risk of death among cirrhotic patients on waiting list for liver transplantation. (March 2023) - Parisse, S.; Martini, A.; Martini, F.; Ferri, F.; Lai, Q.; Lucatelli, P.; Corona, M.; Mennini, G.; Rossi, M.; Corradini, S. Ginanni
Abstract : Background: Liver transplant (LT) candidates are becoming older and more comorbid, with significant increase of metabolic associated fatty liver disease (MAFLD). The Charlson comorbidity index (CCI) is frequently used for risk stratification, even in the LT setting, but not for prediction of waitlist outcomes. We built a new risk score based on comorbidities, named Charlson Metabolic Comorbidity score (CMC-Score), adding within the CCI the clinical features of the metabolic syndrome not present. We then compared the new CMC-Score with the CCI regarding the ability to predict survival on the waiting list. Methods: All consecutive cirrhotic patients listed at our Liver Transplant Center from 2005 to 2019 were retrospectively analyzed. The CMC-Score was constructed by adding one point to the CCI for each clinical variable present among overweight/obesity, arterial hypertension, and dyslipidemia. Fine Gray multivariable competing risk analysis was employed to investigate risk factors for patients' death considering LT as competing event. Results: 385 cirrhotic patients were enrolled, 45% had HCC and 70% had MAFLD. In the multivariate analysis, conducted considering the entire study population, the CMC-Score [SHR=1.260 (95.0%CI= 1.014-1.56); p=0.037], but not the CCI [SHR= 1.005 (95.0%CI=0.811 1.25); p=0.960], was the only statistically significant risk factor for death, adjusting for age, sex, MELDNa and presence of HCC. In a sub-analysis conducted in patients with HCC, the CMC-Score [SHR=1.604 (95.0%CI= 1.145-2.25); p=0.006], but not the CCI [SHR= 1.156 (95.0% CI= 0.815 1.64); p=0.42], was confirmed to be a relevant risk factor for death by adjusting for age, sex, MELDNa and the Up To Seven score of the HCC. Conclusions: The new CMC-Score is useful for identifying patients on the LT waiting list at increased risk of death. Further adjustments in the composition of the score and its validation should be made with multicenter and prospective studies.